ANALYSIS OF THE DETERMINANTS OF THE OPEN UNEMPLOYMENT RATE IN INDONESIA: THE INFLUENCE OF GDP, INVESTMENT, EDUCATION, PROVINCIAL MINIMUM WAGE, AND LABOR FORCE PARTICIPATION RATE IN 2021–2023 - Clarissa Mayang Safira; Arya Dhia Syahputra; Arista Putri Andini; Rizki Mahendra Sandya; Dafi Fachrul Azizi; Ahmad Setiawan Nuraya (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the effect of Provincial Minimum Wage (UMP), Gross Domestic Product (GDP), education, investment, and Labor Force Participation Rate (LFPR) on the Open Unemployment Rate (OUR) across 38 provinces in Indonesia during the 2021–2023 period. This study employs a quantitative approach using secondary data obtained from Statistics Indonesia (BPS), Bank Indonesia, and the Ministry of Investment/BKPM. The analytical method used is panel data regression. Based on the Chow and Hausman tests, the Fixed Effect Model (FEM) was selected as the best estimation model. The empirical results indicate that partially, GDP and UMP have a negative and statistically significant effect on the Open Unemployment Rate. This indicates that an increase in economic growth and appropriate minimum wage policies are effective in stimulating aggregate demand and reducing unemployment. Conversely, investment, education, and LFPR do not show statistically significant impacts on the unemployment rate during the observed period. Simultaneously, all independent variables significantly affect the Open Unemployment Rate in Indonesia, with an Adjusted R-Squared value of 94.88%.